SUHU DAN WAKTU OPTIMUM PROSES EKSTRAKSI ANTOSIANIN DALAM UBI JALAR UNGU (Ipomoea batatas L.) DENGAN ?-L-ARABINOFURANOSIDASE - I N. Wirajana; N. M. T. Juliasari; A.A. I.A.M. Laksmiwati; N. W. Bogoriani (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2019)
Enzyme-assisted extraction (EAE) method is one of the most environmentally friendly methods of enzyme application in the extraction of bioactive compounds. The purpose of this study was to determine the optimum temperature and time required in the extraction of anthocyanin compounds from purple sweet potato (Ipomoea batatas L.) with and without ?-L-arabinofuranosidase (AbfA) - assisted. The AbfA enzyme was obtained from Saccharomyces cerevisiae recombinant strain BJ1824 contain pYHMI-Af plasmid. The optimum temperature and time in the extraction of anthocyanin compound with and without ?-L-arabinofuranosidase from purple sweet potato were performed on the 40, 50, 60 and 700C; and 150, 180, 210 minutes. The extraction was done by ethanol solvent of 60,32% (v/v) acidified with citric acid of 2,39% (b/v). The measurement of anthocyanin levels using UV-Vis Spectrophotometer at 527 nm and 700 nm wavelengths at pH 1,0 and 4,5. The optimum condition of non-enzyme-assisted extraction was at 600C for 210 minutes, with the anthocyanin levels of 26,3842 mg/L; while with the AbfA enzyme-assisted at 500C for 180 minutes, with the anthocyanin levels of 28,2056 mg/L. The extraction with enzyme-assisted resulted the anthocyanin levels of 6,90% higher than without the using of enzyme.